Dendritic cell maturation and antigen presentation in the absence of invariant chain - Rovere, Patrizia (The National Academy of Sciences, 1998)
In immature dendritic cells (DCs), major histocompatibility complex class II molecules accumulate in peptide-loading compartments and, during DC maturation, are exported to the cell surface in response to inflammatory stimuli. Moreover, it has recently been proposed that DCs have specific mechanisms of antigen uptake and delivery into major histocompatibility complex class II-loading compartments. B cells bearing a genetically disrupted invariant chain gene (Ii −/−) show alterations in the transport and function of class II molecules. We herein report that DCs derived from Ii −/− H2(k) but not Ii −/− H2(b) mice undergo normal maturation in response to tumor necrosis factor α and show a high degree of class II surface expression. Class II molecules are accumulated in cathepsin D- and H2-M-positive compartments in immature Ii −/− DC and, during DC maturation, are exported to the cell membrane as compact dimers. Ii −/− DCs present putative Ii-dependent hen egg lysozyme-derived epitopes to T cells. These data support the existence of Ii-independent molecular requirements for class II transport and peptide loading in DCs.